Combination of Green Marketing and Green Products on Purchasing Decisions J. Co Donuts & Coffee (Forward Joint Branch) Katamso Medan - Sartika, Gita Suci; Syahriandy, H.; Marbun, Patar (LPPPIPublishing, 2024)
The combination of Green Marketing and Green Products on purchasing decisions for J.CO Donuts & Coffee (Maju Bersama Branch